LEGAL RIGHTS OF CONSUMER FINANCE AGREEMENT RELATED TO FIDUSIAN GUARANTEE SETTINGS IN THE CITY OF GORONTALO - Nur Insani; Upik Mutiara (Universitas Muhammadiyah Tangerang, 2020)
This study aims to determine the implementation of fiduciary guarantees in financing agreements for motor vehicle purchases and the legal consequences if debtors default in financing the purchase of motor vehicles with fiduciary guarantees at PT. BFI Finance Gorontalo. The research method uses normative legal methods. Data sources consist of primary legal materials, secondary legal materials and non-legal materials. The results showed that the implementation of fiduciary guarantees in motor vehicle financing agreements at PT. BFI Finance Gorontalo is in accordance with Law Number 42 of 1999 concerning Fiduciary Guarantees. Default by the debtor can result in the execution of fiduciary guarantees without having to obtain a court decision because the fiduciary guarantee certificate has the same executorial power as a court decision that has obtained permanent legal force, without having to wait for a court decision, execution can continue to be carried out. If the debtor or fiduciary giver fails the promise, the execution of the object that becomes the object can be done by executing the executable title. If in the implementation of fiduciary collateral execution the transfer of collateral occurs by the debtor, then the PT. BFI Finance Gorontalo can take legal action on accusations of embezzlement of collateral.